Pattern of cervical lesions, with emphasis on precancer and cancer in a tertiary care hospital of Southern India - Gumpeny, Nagamani; Devi, A. Nirmala (International Journal of Research in Medical Sciences, 2017)
Background: Carcinoma cervix is the most common form of cancer in India. Screening is cost-effective but compliance is an issue. Most women present to hospitals at first visit. We studied the pattern of women with carcinoma cervix who presented to the gynecology outpatient department of a large hospital in southern India. Methods: Women attending the gynecology outpatient department of King George hospital were evaluated for the presence of cervical lesions. A complete history was obtained. Biopsies from the cervix were obtained from the aceto-white areas, fixed in 10% buffered neutral formalin. Results: 860 cervical biopsy specimens were received. By routine hematoxylin eosin stains, 180 had precancerous lesions and cancerous lesions with more than two risk factors; in the study period, a total of 253 cervical neoplasms were recorded: 103 were in the pre-cancerous stage (CINU1: 74; 71.84%, CIN II 20/103; 19.41%, CIN III 9/103; 8.73%). Of the 150 cancerous lesions, maximum were SCC non-keratinising (130; 92%). A subset (viz 45/180; 25%) were tested for HPV DNA using Polymerase Cycle Reaction (PCR). The commonest presenting symptom was leucorrhea (40%). Most women reported age of first intercourse below 30 years. On visual examination of cervix, most (25; 55.55%) had exophytic growth and erosion (14; 31.11%). More than 80% (n: 24) presented in stage II and III cancer (n:27). Conclusion: In this hospital based study from a large institution from Southern India, out of 860 cervical biopsy specimens studied, 180 (32.14%) had precancerous lesions and cancerous lesions with more than two risk factors.